Dampak Literasi Kebencanaan terhadap Kesiapsiagaan Peserta Didik dalam Mitigasi Bencana Banjir: Studi di MTsN 4 Magetan - Putri, Dela; Umah, Aulia Mutakhidatul; Fadilah, Aida Amalia; Cahya, Eva Dwi; Ristanti, Arsyiska Nanda; Susilo, Aji (Universitas Pendidikan Ganesha, 2025)
Flood disasters are one of the major challenges faced by various regions in Indonesia, including East Java Province. In the midst of the complexity and vulnerability faced, disaster literacy has been recognized as an important factor in increasing community preparedness, especially among students. This research aims to assess the influence of disaster literacy on students' preparedness in facing flood disasters at MTsN 4 Magetan. This research uses a quantitative descriptive method with an explanatory approach. The sample was taken from class VII students at MTsN 4 Magetan, with a total sample of 100 students selected using a simple random sampling technique. Data analysis was carried out using regression analysis techniques to determine the effect of disaster literacy on students' preparedness. The research results show that disaster literacy has a significant influence on students' preparedness in facing flood disasters by 16.6% and the rest is influenced by other factors not explained in this research.